Comprehensive Assessment of the Progress of «Skoroshkolnik» Technology Implementation. The Individualization of the Adapted Basic Education Program for Pre-schoolers with ASD - G.V. Don; Y.I. Erofeeva; K.R. Salimova; E.Y. Davydova; A.V. Khaustov (Moscow State University of Psychology and Education, 2021)
Present article considers the technology «Skoroshkolnik» which was developed for the individualization of the adapted basic educational program of preschool education of children of senior preschool age in the group of short-term stay, including the individual characteristics of children with autism spectrum disorders (ASD). The program was developed by educational professionals of the Federal Resource Center for the Organization of Comprehensive Support for Children with ASD of MSUPE. Key principles of the technology are shown in accordance with individual characteristics of children with ASD. A pilot study of program effectiveness carried out using a comprehensive assessment of dynamics of basic skills necessary for teaching in a group. To assess goals achievement we used following methods - «Psychological and educational profile (PEP-3)», Vineland Adaptive Behavior Scales (VABS) as well as specially developed tools. The study revealed that the program was effective for basic communication skills, speech, cognitive and motor development, as well as reduced the severity of undesirable behavior and improved behavior regulation.